Association of stress hyperglycemia ratio with short-term and long-term prognosis in patients undergoing coronary artery bypass grafting across different glucose metabolism states: a large-scale cohort study - Zhongchen Li; Runze Chen; Zhiwei Zeng; Peng Wang; Chunyu Yu; Shuo Yuan; Xiaoting Su; Yan Zhao; Heng Zhang; Zhe Zheng (Cardiovascular Diabetology)
Abstract Background Stress hyperglycemia ratio (SHR) is recognized as a reliable indicator of acute hyperglycemia during stress. Patients undergoing coronary artery bypass grafting (CABG) are at high risk of stress hyperglycemia, but little attention has been paid to this population. This study is the first to investigate the association between SHR and both short-term and long-term prognosis in CABG patients, with a further exploration of the impact of SHR across different glucose metabolic states. Methods A total of 18,307 patients undergoing isolated CABG were consecutively enrolled and categorized into three groups based on SHR tertiles. The perioperative outcome was defined as a composite of in-hospital death, myocardial infarction, cerebrovascular accident, and reoperation during hospitalization. The long-term outcome was major adverse cardiovascular and cerebrovascular events (MACCEs). Restricted cubic spline and logistic regression linked SHR to perioperative risks. Kaplan–Meier and Cox regression analyses were used to determine the relationship with long-term prognosis. Subgroup analyses were further conducted based on different glucose metabolic states. Results A U-shaped association was observed between SHR and perioperative outcome in the overall population (P for nonlinear < 0.001). As SHR increased, the risk of perioperative events initially decreased (OR per SD: 0.87, 95% CI 0.79–0.97, P = 0.013) and then elevated (OR per SD: 1.16, 95% CI 1.04–1.28, P =  0.004), with an inflection point at 0.79. A similar U-shaped pattern was identified in patients with normal glucose regulation. Among those with prediabetes, the association was J-shaped, while in patients with diabetes, the association became nonsignificant when SHR exceeded 0.76. Adding SHR to the existing risk model improved the predictive performance for perioperative outcomes in the overall population (AUC: 0.720 → 0.752, P < 0.001; NRI: 0.036, P =  0.003; IDI: 0.015, P < 0.001). For long-term outcomes, the risk of events was monotonically elevated with increasing SHR, regardless of glucose metabolic status. The third tertile showed a 10.7% greater risk of MACCEs (HR: 1.107, 95% CI 1.023–1.231, P =  0.024). Conclusions SHR was significantly associated with prognosis in CABG patients, demonstrating a non-linear U-shaped relationship with short-term outcomes and a linear positive association with long-term outcomes. The in-hospital risk associated with SHR was attenuated in patients with diabetes. Graphical abstract CABG, coronary artery bypass grafting; CI, confidence interval; DM, diabetes Mellitus; HR, hazard ratio; MACCE, major adverse cardiovascular and cerebrovascular events; NGR, normal glucose regulation; OR, odds ratio; Pre-DM, prediabetes; SHR, stress hyperglycemia ratio Research insights What is currently known about this topic? Stress hyperglycemia is common during the perioperative period in CABG patients and is linked to adverse short- and long-term outcomes. The stress hyperglycemia ratio (SHR) is a novel metric that accounts for baseline glycemia to better reflect acute stress-induced hyperglycemia. However, SHR has not been studied in the CABG population. What is the key research question? This study is the first to investigate the association between SHR and both short-term and long-term prognosis in patients undergoing CABG, while further exploring its impact across different glucose metabolic states, categorized as normal glucose regulation, prediabetes, and diabetes. What is new? In CABG patients, SHR shows a U-shaped relationship with perioperative events and a linear positive association with long-term outcomes, both of which are modulated by glucose metabolic status. How might this studyinfluence clinical practice? Findings support the incorporation of SHR for risk stratification and personalized glucose management in CABG patients, ultimately improving both in-hospital and long-term prognosis.